COMPARATIVE EFFECTIVENESS OF IN VITRO FERTILIZATION PROGRAMS AFTER TREATMENT OF ENDOMETRIOID OVARIAN CYSTS BY LAPAROSCOPIC EXCISION AND REDUCTION THERAPY - Семен Вадимович Зотов; Полина Юрьевна Мотырева; Виталий Михайлович Кулешов; Борис Исаевич Айзикович; Виктория Васильевна Лихачева; Сергей Николаевич Филимонов (The Publishing House Medicine and Enlightenment, 2021)
The effectiveness of assisted reproductive technology (ART) programs in patients after surgical treatment of endometrioid ovarian cyst (EOC) and after transvaginal EOC was compared. The study group consisted of 47 patients who underwent the ART program after EOC puncture, and 48 patients who entered the ART program after surgical treatment of EOC by laparoscopic exfoliation of the cyst capsule using electrocoagulation. The control group consisted of 50 patients with male factor infertility. The results of the study showed that in the group of punctured patients, the timing of entry into ART programs is significantly less than in the surgical treatment of EOC. The number of obtained oocytes, zygotes and blastocysts of good quality is statistically higher in the group of punctured patients compared to the operated patients and is comparable with the control group. The «Baby take-home rate» did not differ in the group of dotted patients and in the control group, while significantly decreasing after laparoscopy.